The work of director Spike Jonze a collection of music videos, short films, documentaries, and rarities - Acord, Lance 1964- (Palm Pictures [u.a.], 2003)
Spike Jonze is most widely known as the director of Being John Malkovich and Adaptation. However, Jonze also remains a pioneer in the world of music videos and for many years has been best known as an award-winning music video, short film and commercial director.
Original: USA 2003
A Side: Music Videos: California Wax; Sur shot Beatie Boys; Drop The Pharcyde; Cannonball The Breeders (Co-directed with Kim Gordon); Sabotage Beastie Boys; Da Funk Daft Punk; What's up Fatlip ? Fatlip; Undone (The Sweater Song) Weezer; Praise you Fatboy Slim (Directed by the Torrance Community Dance Group with Roman Coppola); Feel the Pain; Dinosaur Jr.; If I only had a brain MC 900ft JEsus; Sky's The Limit The Notorious B.I.G.; Weapon of choice Fatboy Slim; Buddy Holly Weezer; Elektrobank The Chemical Brothers; It's oh so queit Björk; The Interviews - musicians discuss the music videos; Making of drop with the Pharcyde - interviews and behind-the-scenes; Audio Commentaries from Fatboy Slim, Weezer, The Pharcyde; Daft Punk, The chemical Brothers, Björk, Christopher Walken, Puffy and more. Also includes Beastie Boys commentary on a selection of the videos
B Side: Rarities: How they get there - a short film with Mark Gonzales; Mark Paints - another short film with Mark Gonzales; The oasis Video that never heppened; Rockafella Skank - Richard Koufey's audition tape for Fatboy Slim; The Woods - a short film excerpt fom Mouse, a Girl Skateboards film ; Documentaries: What's up fatlip ? (the documentary) - After Fatlip left The Pharcyde, outrageous rumors began circulating. This candid documentary happened as Spike and Fatlip worked together on a music video, and Spike let his curiosity take over. (31 min.); Amarillo by morning - while filming pro bull riders at a national rodeo in Houston, Spike befriended two suburban teenagers who aspired to be cowboys. This chronicles a day in their life. (29 min.); Torrance Rises - Torracne Community Dance Group on the road to their grand performance at the MTV Video Music Awards (34 min.) - includes A 52 Page Book with Spike's photographs, drawings and interviews
Keywords: Jonze, Spike; Jonze, Spike -- 1969-; Music videos -- Production and direction; Dokumentarfilm; Musikvideo; Kurzfilm; DVD-Video; Documentary films - United States; Fiction films; Filmed interviews; Music videos; Rock videos; Short films